INTEGRATION OF ACUPUNCTURE AND STANDARD MEDICAL TREATMENT FOR A GERIATRIC PATIENT WITH POST-PAROTIDECTOMY FACIAL NERVE PARALYSIS: A CASE REPORT - Supriyana, Dwi Surya; Prasetyawati, Arsita Eka; Budianto, Pepi (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2026)
Background: Acupuncture is an established treatment for peripheral facial nerve paralysis, but optimal management of post-parotidectomy facial nerve paralysis in the geriatric population remains uncertain. Case Report: A 60-year-old man developed right facial nerve paralysis following parotidectomy and received integrated care from a medical acupuncturist, neurologist, and family physician with corticosteroids, mecobalamin, other oral medications, and acupuncture. Electroacupuncture (EA) and manual acupuncture (MA) were given twice weekly for 30-minute sessions (28 sessions), resulting in progressive improvements: lagophthalmos resolved by session 7, mouth symmetry improved by session 20, and eyebrow movement was stored by session 28. Conclusions: House-Brackmann Facial Nerve Grading System (HBFNGS) and nerve conduction velocity (NCV) testing demonstrated functional recovery, suggesting that combined electroacupuncture, manual acupuncture, and pharmacotherapy may be effective for post-parotidectomy facial nerve paralysis.